Phase-Locked loops lock-in range in Frequency Modulated-Atomic Force Microscope nonlinear control system - Bueno, Atila Madureira; Balthazar, José Manoel [UNESP]; Castilho Piqueira, Jose Roberto (Elsevier B.V., 2012)
Since the mid 1980s the Atomic Force Microscope is one the most powerful tools to perform surface investigation, and since 1995 Non-Contact AFM achieved true atomic resolution. The Frequency-Modulated Atomic Force Microscope (FM-AFM) operates in the dynamic mode, which means that the control system of the FM-AFM must force the micro-cantilever to oscillate with constant amplitude and frequency. However, tip-sample interaction forces cause modulations in the microcantilever motion. A Phase-Locked loop (PLL) is used to demodulate the tip-sample interaction forces from the microcantilever motion. The demodulated signal is used as the feedback signal to the control system, and to generate both topographic and dissipation images. As a consequence, a proper design of the PLL is vital to the FM-AFM performance. In this work, using bifurcation analysis, the lock-in range of the PLL is determined as a function of the frequency shift (Q) of the microcantilever and of the other design parameters, providing a technique to properly design the PLL in the FM-AFM system. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Frequency-Modulated Atomic Force; Microscopy; Phase-Locked loops; Bifurcation; Nonlinear dynamics; Mathematical model